Aneroid Sphygmomanometers: Do They Need Regular Inspection? - Gaamangwe, Tidimongo; Sala, Jean-Louis; Krivoy, Agustina; Lawes, Peter; Herzog, Clarence; Mathews, Bindu (CMBES Proceedings, 2006)
Aneroid sphygmomanometers are some of the simplest, yet vital, diagnostic medical devices still used in healthcare. They have been used for blood pressure measurements for decades because of their simplicity. Although they fall under the classification of medical equipment, their management generally varies from other medical equipment because they are simple and mechanical. A number of departments that manage aneroid sphygmomanometers rely on users to report inaccuracies. In most cases they are not tested regularly because it is assumed that they are reliable. However, a number of studies have shown that aneroid sphygmomanometers are susceptible to linearity errors. This paper presents results of a study that was undertaken in the Winnipeg Regional Health Authority to establish how aneroid sphygmomanometers are managed and whether they need to be placed on a regular inspection program. Results from other facilities in Canada are also presented for comparison.